COLLABORATIVE GOVERNANCE DALAM PENANGANGAN PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (Studi Kasus : PMKS Golongan Anak Pada Dinas Sosial Provinsi DKI Jakarta) - Marsyah Tianty; Uchaimid B.Robby; Saefudin Zuhri (PANDITA : Interdisciplinary Journal of Public Affairs, 2021)
Handling of Children with Social Welfare Problems cannot be handled by one agency or institutions. Therefore, it is needed collaborative with stakeholders. The purpose of the research is to find how is collaborative governance in handling of childern with sosial welfare problems at Department Social Service in DKI Jakarta Province. The theory used in collaborative governance proposed by Ansell and Gash, that is Initial Conditions, Institusinal Design, Facility Leadership and Collaborative Processes comprising face to face, dialogue advance, bild trush, commitment in collaboration and mutual understing.The research method used is qualitative research, data collection techniques are observation, interviews and documentation related to research. The results of this study explain that collaborative governance has been running quite good based on the initial condition phenomenon, facility and process leadership collaboration. in the implementation of collaborative governance , there are factor support, such as a sense of shared concern, informed data and problems that canot be resolved alone so it mush involve the role of the government, the community and private sectors